Lives for Sale: Human Trafficking - Films Media Group (2006)
Each year, more than one million people try to cross the U.S.-Mexico border, contending with dangerous forces that prey on their hopes and exploit their gullibility. This program exposes the most painful, disturbing, and hidden dimension of illegal immigration: the growing black market trade in human beings. Shedding light on the poverty that causes so many to risk everything by leaving their home countries, the film reconstructs the frightening journeys of sex-slavery victims and highlights the work of CAST-the Coalition to Abolish Slavery and Trafficking. Border patrol agents and other members of law enforcement share their knowledge and experience regarding this ongoing human rights crisis. (60 minutes).
fma39008
Mode of access: World Wide Web.
System requirements: Windows Media, etc.